2000
DOI: 10.1111/j.1151-2916.2000.tb01227.x
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray Computed Tomography and Mercury Porosimetry for Evaluation of Density Evolution and Porosity Distribution

Abstract: X-ray computed tomography (CT) and mercury porosimetry were combined to connect density gradients and the distribution of open porosity in a sintered compact. CT clearly showed that open porosity follows the initial distribution of low-density zones. Mercury porosimetry detected three distinct levels of porosity. Microstructural examination correlated the porosity level with the coordination of (i) two to three or (ii) multiple grains around pores. This combination of techniques provides a novel tool for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…the sum of the material volume and that of unconnected pores. Based on the estimated material density r mat , the closed porosity of the strut material is e strut À e eff;strut ¼ 1 À r a r mat ¼ 0:123 AE 0:047 (15) This result is relevant to both the meso-and the microscale. Because the sample was crushed, no macroscale features were retained.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…the sum of the material volume and that of unconnected pores. Based on the estimated material density r mat , the closed porosity of the strut material is e strut À e eff;strut ¼ 1 À r a r mat ¼ 0:123 AE 0:047 (15) This result is relevant to both the meso-and the microscale. Because the sample was crushed, no macroscale features were retained.…”
Section: Methodsmentioning
confidence: 88%
“…14 X-ray tomography, in combination with Hg porosimetry, has been used for the characterization of porous media. 15,16 Microscale tomography using destructive focused ion beam (FIB) tomography has been carried out for the nanocharacterization of particulate systems. [17][18][19] 3D digital representations from tomographic scans of porous media have been used for the determination of lineal path distributions, 20 cord length distributions, 20 and local porosity distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Although ceramic granules do not experience fracture in the same conveniently distinctive manner as silica particles, they do undergo internal decreases in the spacing between the ultimate particles. 3,4 This provides a mechanism by which local density is limited: the ultimate particles themselves can form close-packed structures that resist further deformation. As before, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Recently, mercury porosimetry in combination with X-ray computed tomography (XRCT) has confirmed that low-density (LD) zones within such compacts are more likely to retain open porosity during sintering. 4 Although connections between overall density and grain size have been established for some time, 5,6 it has been proved only recently that the initial green state uniformity controls localized final grain size and external dimensions. 3 As a tool to monitor the compaction behavior of the agglomerated powders used by industry, the compaction curve (i.e., density versus the logarithm of pressure) has been quite useful 7 in defining three different regimes widely believed to be the result of asynchronous mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of mercury porosimetry and X-ray computerized tomography has been reported recently in the literature (11,12,21) and been used to determine mineral-specific porosity distributions, inhomogeneous penetration of the mercury and the nonuniform spatial variation of open porosity during sintering of ceramic green bodies. Due to the high density of mercury and, therefore, cross section of mercury for scattering X-rays and the pronounced hysteresis between MIP intrusion and extrusion curves of cement-based materials, mercury entrapment can be made visible by X-ray tomographic techniques (Fig.…”
Section: X-ray Tomographymentioning
confidence: 99%